Matrix Metalloproteinases-1 and -8 Improve the Distribution and Efficacy of an Oncolytic Virus - Mok, Wilson; Boucher, Yves; Jain, Rakesh K. (Cancer research (Chicago, Ill.), 2007)
Oncolytic viral vectors show enormous potential for the treatment of many solid tumors. However, these vectors often suffer from insufficient delivery within tumors, which limits their efficacy in both preclinical and clinical settings. We have previously shown that tumor collagen can significantly hinder diffusion, and that its degradation can enhance the distribution and efficacy of an oncolytic herpes simplex virus (HSV) vector. Here, we identify two members of the matrix metalloproteinase (MMP) family of enzymes, MMP-1 and MMP-8, which can modulate the tumor matrix and enhance HSV delivery and efficacy. We show that overexpression of MMP-1 and MMP-8 in the human soft tissue sarcoma HSTS26T leads to a significant depletion of tumor-sulfated glycosaminoglycans. This increases the hydraulic conductivity of these tumors and enhances the flow of virus during injection. In control tumors, injected virus accumulates primarily in the periphery of the tumor. In contrast, we observed a more widespread distribution of virus around the injection site in MMP-1– and MMP-8–expressing tumors. Due to this enhanced vector delivery, MMP-expressing tumors respond significantly better to oncolytic HSV treatment than control tumors. Thus, these findings introduce a new approach to improve the delivery and efficacy of oncolytic viral vectors: modulation of tumor glycosaminoglycans to enhance convection. [Cancer Res 2007;67(22):10664–8]